Epidemiological study of novel coronavirus (COVID-19): macroscopic and microscopic analysis - Hembram, K. P. S. S.; Kumar, Jagadish (International Journal Of Community Medicine And Public Health, 2021)
Background: This study aimed to unravel the microscopic behaviour by introducing health functional for individuals during coronavirus (COVID-19) epidemic and understand the macroscopic behaviour of epidemic infection dynamics by growth models. Methods: Virus strength, immunity and medications are taken as independent parameters for health functional in the stochastic simulation for microscopic investigation. For macroscopic understanding, Logistic, Weibull and Hills growth models are considered to obtain power indices. Results: Microscopically, the effect of medication that inhibits virus strength with increasing immunity is shown through the simulation. While, without medication and increasing viral strength lead the individual to death, improved medication and increasing immunity strength lead back to normal life. Macroscopically, scale invariance of power indices over time reveals similarity of spreading of infection in most of the countries. Conclusions: Proper medication needs urgency for the infected person to keep the health well. Overall this issue warrants federal policy to maintain the social distance, public awareness to prevent the infection, and healthcare facilities for early detection by tracing the infected people for potential treatment.